Developing Prototype of Modbus IoT Gateway for Odoo ERP Integration - Apriando, Daniel Yosh; Tenggono, Alfred (International Journal of Informatics and Computation, 2026)
Industrial environments increasingly require seamless integration between field-level devices and enterprise management systems to support real-time monitoring and operational decision-making. However, many industrial devices still rely on the Modbus RTU protocol, which limits direct interoperability with modern Enterprise Resource Planning (ERP) platforms. This paper develops a prototype of a Modbus IoT Gateway for Odoo ERP integration to bridge this communication gap. The proposed system utilizes an ESP32 controller as a Modbus master, Node-RED as middleware, and Odoo ERP as the centralized monitoring and management platform. The gateway acquires data from field devices, converts the information into JSON format, and transmits the data securely through a WPA2-protected wireless network for integration with the ERP system. This study implements a fixed 10-second transmission interval to support near real-time data synchronization while maintaining efficient resource utilization. The system continuously monitors Electrical Conductivity (EC), pH values, relay status, and robotic arm conditions. The acquired data are processed by Node-RED and stored in the Odoo database for visualization and analysis. The Odoo dashboard presents operational information through dynamic graphs and status indicators, enabling operators to observe parameter trends, detect abnormal conditions, and respond promptly to potential operational issues. The implementation results demonstrate successful end-to-end integration between Modbus-based industrial devices and the Odoo ERP platform. The proposed architecture provides reliable data acquisition, secure communication, centralized monitoring, and automated operational supervision. The system improves operational visibility and supports faster decision-making through near real-time information delivery. These findings indicate that the proposed Modbus IoT Gateway offers a practical and scalable solution for integrating industrial automation systems with enterprise applications.